Cardioprotective Activity of Ethanolic Extract of Temu Giring in Male Wistar Rats Induced by Isoproterenol - Jekson Martiar Siahaan; Ratih Praseti Yanti; Endy Juli Anto; Syafruddin Ilyas; Binarwan Halim (Jurnal Ners, 2026)
Coronary heart disease is one of the leading causes of death worldwide. One manifestation is myocardial infarction, a condition of heart muscle damage due to obstructed blood flow. This study aims to analyze the extract of temu giring to show a decrease in cardiac enzyme levels (CK-MB, LDH) that increase due to ISO with the title cardioprotective activity of temu giring ethanol extract in rats induced by isoproterenol. The research method used an experimental approach in male Wistar rats divided into a control group and an isoproterenol induction treatment group. Induction was carried out with a certain dose and duration of exposure according to standard protocols. Parameters measured included cardiac biomarker levels and myocardial tissue histopathology. The results showed that the treatment given to group 2 caused the most severe heart damage in rats, which was characterized by the highest cardiac histopathology score and a significant increase in CKMB and ST2 levels compared to the control group and other treatment groups. Groups 3 to 6 experienced a significant increase in CKMB and ST2 levels compared to the control group, but the histopathological damage to the heart in these groups was relatively mild and did not differ significantly from each other. The biomarkers CKMB and ST2 were effective in detecting damage and stress in rat hearts, and were consistent with histopathological findings as parameters for assessing heart damage. Isoproterenol induction effectively caused myocardial infarction in Wistar rats.